Is greater decisionmaking power of women associated with reduced gender discrimination in South Asia? - Smith, Lisa C.; Byron, Elizabeth (International Food Policy Research Institute, 2005)
Recent research has shown that improving women’s decisionmaking power relative to men’s within households leads to improvements in a variety of well-being outcomes for children. In South Asia, where the influence of women’s power is particularly strong, these outcomes include children’s nutritional status and the quality of feeding and health care practices. Focusing on nutritional status, this paper presents the results of a study investigating whether increases in women’s power have a stronger positive influence on the nutritional status of their daughters than their sons. If so, then increasing women’s power not only improves the well-being of children as a group, but also serves as a force to reduce long-standing discrimination that undermines female capabilities in many important areas of life as well as human and economic development in general. To investigate this issue, the study draws on Demographic and Health Survey data collected during the 1990s in four countries: Bangladesh, India, Nepal, and Pakistan. The main empirical technique employed is multivariate regression analysis with statistical tests for significant differences in effects for girl and boy children. A total of 30,334 women and 33,316 children under three years old are included in the analysis. The study concludes that, for the South Asia region as a whole, an increase in women’s decisionmaking power relative to men’s, if substantial, would be an effective force for reducing discrimination against girl children. However, this finding is not applicable in all countries and for all areas and age groups of children. Indeed the study finds evidence that in some areas, for instance the northern and western states of India as a group, increasing women’s power would lead to a worsening of gender discrimination against girls. This is likely the result of deeply embedded son preference associated with highly patriarchal social systems. The lesson for policymakers and development practitioners is that while increasing women’s power is likely to improve the well-being of children, in some geographical areas it will not necessarily diminish discrimination against girls, which violates human rights and undermines the region’s economic development and the health of its population. In these areas, to overcome son preference, economic returns to girls will have to be increased and efforts to change customs regarding marriage and inheritance associated with patriarchal kinship systems, which favor males, will have to be made.